Comparison Of Mosquito Larvicidal Activity Of Annona Squamosa Leaves Growing In Different Eco-Zones In Tanzania - B. DANIEL; E. INNOCENT; Z.H. MBWAMBO; S.G.MUSHARRAF (International Journal of Pharma and Bio Sciences, 2011)
Annona squamosa L. (Annoneceae) is a medicinal plant widely distributed in all eco-zones of Tanzania. The plant has a wide use as medicine, food and insecticide. A qualitative study of ethanolic extracts of A. squamosa collected from different eco-zones was done using HPTLC. Furthermore, each leaf ethanolic extract and leaf powders were screened for mosquito larvicidal activity against larvae of Culex quinquefasciatus Say and An. gambiae s.s. The results from HPTLC showed almost the same kind of compounds based on their retention factor as observed in both long and short wavelength. The leaf ethanolic extract and leaf powders from Brachystegia Julbernadia Savanna Woodlands eco-zone (T6) showed the highest larvicidal activity with LC50 value of 0.0066 mg/ml and 0.0860 mg/ml against Culex quinquefasciatus while activity of the same sample against An. gambiae was 0.0252 mg/ml and 0.0599 mg/ml respectively after 24 h of exposure. Phytochemical screening of DCM, EtoAc and ButOH fractions obtained from T6 leaf ethanolic extract indicated the presence of alkaloids, terpenoids and flavanoids. The results suggest that A. squamosa from T6 eco-zone is the most rich chemotype agent for mosquito control.